Ammonites and the mid-Cretaceous saga - Bengtson, Peter; Kakabadze, Mikheil (Cretaceous research, 2018)
Ever since the introduction of the Cretaceous System, nearly two centuries ago, the terms ‘mid-Cretaceous’ and ‘middle Cretaceous’ keep appearing in the literature, implying a three-fold division rather than the more generally accepted two-fold division of the system/period. The frequent and persistent use of these informal terms proves that they fulfil a need in stratigraphic communication; consequently, formalisation of a middle series/epoch of the Cretaceous System/Period is justified and desirable and will put an end to the present terminological confusion with respect to division of the Cretaceous. According to long-established practice, biotic turnover events (major extinctions and/or radiation events) of biostratigraphically significant fossil groups provide convenient, correlatable horizons for positioning chronostratigraphic boundaries. As a first step towards establishing a solid database for a formal proposal for a three-fold division of the Cretaceous, taxonomic turnover events at the level of family- and genus-group taxa (families/subfamilies and genera/subgenera) for the historically most important fossil group, the ammonites, have been analysed for the broad ‘mid-Cretaceous’ interval, ranging from base Barremian to base Santonian. The results provide little support for a series boundary at the traditional Lower-Upper Cretaceous boundary at the base of the Cenomanian. Instead, the most significant ammonite turnover event occurred at the Aptian-Albian boundary interval, which then emerges as a potential lower boundary of a middle Cretaceous series. Higher in the Cretaceous, no similarly distinctive turnover event is recorded for the ammonites, although the turnover at the Cenomanian-Turonian boundary interval is slightly more pronounced. For a formal proposal for a three-fold division of the Cretaceous, the ammonite data need to be integrated with data on other chronostratigraphically significant fossil groups, such as inoceramid bivalves, foraminifers, calcareous nannofossils and dinoflagellates, and with magnetostratigraphy, chemostratigraphy and cyclostratigraphy.